„Tušti titulai“ ir tikrieji vardai: LDK protestantų į(si)vardijimai senojoje raštijoje - Pociūtė, Dainora (Literatūra, 2015)
The article discusses the confessional identity of the protestants of the Grand Duchy of Lithuania and its definition in the official documents and popular religious literature of the 16–17th century. The article questions the permanent aim of historians to necessarily relate the processes of early evangelism in GDL to a specific doctrine of Lutheranism, Cvinglism, Calvinism. The article mentions that from the beginning of the Reformation all names used for evangelicals were derived from the official environment of the Roman church and were of the eponymic (related to the name) origin, and were quite offensive. The term Lutheran was a most favoured definition of all Reformation period heresies in the early Roman catholic use, therefore a historian cannot rely on the assumption that such a name defines the confessional identity of those times.The article discusses the definition of the confessional identity of Lithuanian protestants. It is noticed that in the early documents of GDL during the reformation period (1543–1566) the GDL protestants avoided any links of their organisations to the confessions of Augsburg or Switzerland and referred to themselves and their churches as the Christian denominations by juxtaposing them to the confession of the Roman Catholics. However, after the death of knight M. Radvilas the Black in 1566 Mikalojus Pacas published Confession of faith and its annexes related the doctrine confessed by GDL protestants with the religion of Helvets and applied the definition of Saxon and Augsburg religion to Lutheran confession. From 80’s of the 16 century the term Evangelical became to be used together with Christian in the popular works of protestants, whereas at the end of the century the official GDL documents associate their church with the Reformed Church.Nevertheless, despite the facts that eponyms used by Catholics were offensive, in the long run many of them became used among the protestants themselves. At the beginning they were applied only to describe the representatives of other confessions, however from the 17th century they started calling themselves Calvinists or the representatives of the Calvinist confession. This process is clearly witnessed by the testaments of GDL reformers and some other official documents, but not the mass church written works, which used Christian and Evangelic terms. Only in the use of 18th century the compound of two words became used, which is still popular today – Reformed evangelicals. In such a way the eponymic origin of the term was dropped out to describe confessional identity and reflected the authentic nature of the GDL Reformed church.